SOCIAL MEDIA MANAGEMENT BY GOVERNMENT AGENCIES IN THE PERSPECTIVE OF LEGISLATION IN INDONESIA - Tukunang, Michael (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
In the digital era, Indonesian government agencies increasingly utilize social media as an official instrument of public communication, information dissemination, and citizen engagement. However, its management raises various legal and governance challenges, including message inconsistency, ethical violations, misinformation, personal data risks, and potential breaches of cyber regulations. This study aims to analyze the legal framework governing government social media management in Indonesia and evaluate its alignment with applicable legislation. Using a normative juridical approach, this research examines relevant laws, including the Law on Public Information Disclosure, the Law on Electronic Information and Transactions and its amendments, the Law on Personal Data Protection, and Ministerial Regulation Number 83 of 2012. The findings indicate that although Indonesia possesses an adequate legal foundation, implementation gaps persist due to regulatory ambiguity, limited technical supervision, and insufficient human resource capacity. Strengthening governance requires regulatory updates, standardized operating procedures, enhanced digital literacy, and integrated monitoring mechanisms. Optimized governance will ensure accountability, transparency, legal compliance, and the protection of citizens’ rights, thereby enhancing public trust and supporting democratic digital transformation in Indonesia.